Digitalisasi Pemasaran Produk Ladrang Lele Sebagai Komoditas Unggulan Desa Tambuko, Guluk-Guluk, Sumenep - Maksum (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
ABSTRACT The availability of many springs in Tambuko Village has initiated the community to cultivate catfish. The Tambuko Village community has a Panji Laras Fish farming group consisting of several local communities who cultivate catfish. The Covid-19 pandemic has reduced consumer demand for fresh catfish, resulting in unsold cultivation products. The steps taken by the people of Tambuko Village to deal with this problem are to produce catfish-based snack products. One of the products produced is